2021
DOI: 10.1088/1755-1315/746/1/012022
|View full text |Cite
|
Sign up to set email alerts
|

Mangrove cluster as adaptation pattern of mangrove ecosystem in Segara Anakan Lagoon

Abstract: Segara Anakan Lagoon (SAL) as the specific ecosystem is arranged by the mangrove ecosystem and lagoon ecosystem. The mangrove ecosystem in SAL needs high adaptation to reduce the impact of water tide, water inundation, water salinity, and other factors. This research aimed to analyze mangrove clustering in Segara Anakan Lagoon. The method of this research used Hierarchical Clustering Methods based on mangrove density to analyze cluster adaptation of the mangrove ecosystem. The result showed that (1) The mangro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 7 publications
0
21
0
Order By: Relevance
“…The area had water temperature between 25.0-30.5 o C, water salinity between 6.0-7.5 ppt, water pH of 5.0-6.4, soil pH between 6.0-7.0 with a muddy clay texture, soil nitrate of 11.5-14.5 mg/l, soil phosphate between 8.2-16.0 mg/l and soil pyrite of 1.0-3.0%. This data is not different from Hilmi et al (2021a) which reported that the mangrove ecosystem in Segara Anakan had physical and chemical properties of soil nitrate between 10.0-22.0 mg/l, soil pH between 5.7-6.92, soil texture of clay, loam, loamy clay, mud and mud clay, soil phosphate between 6.85-17.65 mg/l, soil pyrite between 1.03-3.10%, water pH between 5.6-7.07, and water salinity between 0-40 ppt. These conditions show that both studied sites on the north coast of Jakarta and Segara Anakan had a similarity of environmental factors to support mangrove growth.…”
Section: Physical and Chemical Parametersmentioning
confidence: 46%
See 3 more Smart Citations
“…The area had water temperature between 25.0-30.5 o C, water salinity between 6.0-7.5 ppt, water pH of 5.0-6.4, soil pH between 6.0-7.0 with a muddy clay texture, soil nitrate of 11.5-14.5 mg/l, soil phosphate between 8.2-16.0 mg/l and soil pyrite of 1.0-3.0%. This data is not different from Hilmi et al (2021a) which reported that the mangrove ecosystem in Segara Anakan had physical and chemical properties of soil nitrate between 10.0-22.0 mg/l, soil pH between 5.7-6.92, soil texture of clay, loam, loamy clay, mud and mud clay, soil phosphate between 6.85-17.65 mg/l, soil pyrite between 1.03-3.10%, water pH between 5.6-7.07, and water salinity between 0-40 ppt. These conditions show that both studied sites on the north coast of Jakarta and Segara Anakan had a similarity of environmental factors to support mangrove growth.…”
Section: Physical and Chemical Parametersmentioning
confidence: 46%
“…Therefore, the environmental data (salinity, pH, nitrate, phosphate, and soil texture) suggest that the studied area in north Jakarta had good suitability for supporting mangrove growth (Abdelhakeem et al 2016;Barreto et al 2016;Hilmi et al 2020;Hilmi et al 2017a;Hilmi et al 2021b;Tam et al 2009). Based on the salinity level, the water studied on the north coast of Jakarta could be defined as brackish water (Djohan 2012;Hilmi et al 2021a;Kusmana and Maulina 2015;Wang et al 2019). Furthermore, the data of nitrate and phosphate also indicated that the mangrove ecosystem had good fertility to support mangrove growth (Sharafatmandrad and Mashizi 2020).…”
Section: Physical and Chemical Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…Meanwhile, according to Priosambodo et al (2019), Composition and structure of mangrove vegetation in Tamo rocky cliff beach Majene West Sulawesi dominated by monoculture stake of R. stylosa which is an important value index range between 182.90 -300. Sari et al (2021). The mangrove forests in Jakarta Bay have an average Important Value Index (IVI) for all levels of life stage 95.7 with the mangrove forests were dominated by A. marina, Avicennia lanata, R. apiculata, Sonneratia caseolaris, and S. alba.…”
Section: Discussionmentioning
confidence: 99%